ANALYSIS OF MARKETING STRATEGIES FOR CABBAGE VEGETABLES (Brassica oleracea L. var. cagitata L) AT JETIS AGRIBUSINESS SUB TERMINAL (STA) SEMARANG REGENCY - Istanto, Istanto; Hilmi Arija Fachriyan, Hilmi Arija (MEDIAGRO, 2023)
ABSTRACTThe purpose of this research is to determine the marketing strategy of cabbage in Jetis Agribusiness Sub Terminal (STA), Semarang Regency. This research method is a qualitative descriptive method using primary and secondary data. Data collection by way of observation, interviews and questionnaires. The research location was determined deliberately, namely in the Jetis Agribusiness Sub Terminal (STA), Semarang Regency. Respondents consisted of farmers, cabbage traders, consumers and employees of the Jetis Agribusiness Sub Terminal (STA). Methods of determining respondents by means of Purposive and Accidental Sampling. The number of respondents was 58 people. Taking respondents with purposive method. consisting of 5 respondents from wholesalers, and 3 respondents from Jetis Agribusiness Sub Terminal (STA) employees. Whereas with the Accidental Sampling method, 5 respondents were farmers, 10 respondents were middlemen traders, 15 respondents were collectors, 15 respondents were retailers, and 5 respondents were consumers. Based on the results of the analysis of internal and external factors, the coordinate points (1.998 : 1.536) are obtained, which are in quadrant I, so the choice of strategy is Aggressive strategy or SO (strengths-opportunities) strategy. The alternative marketing strategies for cabbage in the Jetis Agribusiness Sub Terminal (STA) are 1) Improving transportation facilities and infrastructure, 2) Maintaining the comfort of the Jetis Agribusiness Sub Terminal (STA), 3) Increasing promotion and information, 4) Increasing the function of the Sub Terminal facilities Jetis Agribusiness (STA), and 5) Maintain product availability.  Keywords: Cabbage and Marketing Strategy.